Phytochemical composition of Blumea lacera leaf and its inhibitory effects on the activity of enzymes related to metabolic diseases - Mohammad Rowshanul Habib; Yasuhiro Igarashi; Mohammad Ahasanur Rabbi (Faculty of Pharmacy, Mahidol University, 2022)
Blumea lacera (Bum. f.) DC is an important medicinal plant of Bangladesh having several ethnomedicinal values. To give the scientific basis of ethnomedicinal uses, the present study analyzed phytochemical composition of methanol extract of B. lacera leaves (designated as MBLE) and evaluated its inhibitory effects on pancreatic lipase, α-amylase, xanthine oxidase (XO) and angiotensin I-converting enzyme (ACE). Different in vitro methods were used to perform enzyme inhibition assays for MBLE and its phytochemical profile was analyzed by GC-MS. In case of all the enzyme inhibition assays, the percentage of inhibition by MBLE was increased with increasing in concentrations. Among these enzymes, MBLE showed strong activity (IC50:13.34±1.05 μg/mL) against ACE as compared with captopril (IC50:8.09±0.74 μg/mL) used as standard reference whereas it exhibited moderate activity against other enzymes. The IC50 values of MBLE were found to be 9.87±0.25, 40.17±2.32 and 93.88±5.21 μg/mL for pancreatic lipase, α-amylase and XO, respectively. In addition, some compounds identified in MBLE by GCMS, were also consistence with these enzyme inhibitory activities. Thus, this study demonstrates the enzyme inhibitory potentials of B. lacera leaves for the first time and it might be a potential tool for the treatment of metabolic diseases.